A comprehensive evaluation of the parameters that affect the performance of in-situ gelation system. (1st August 2018) - Khamees, Tariq K.; Flori, Ralph E.
Highlights: This study highlighted the importance of studying several parameters that could affect the gelation process of in-depth gel treatment using numerical modeling by UTGEL simulator. Using one quarter of five spot with eight layers, a numerical model was built. The injection rate for most of runs was 1070 bbl/day. The gelant solution was injected for 50 days only into high-permeability layers, which were located in the middle of the model. Shear thinning and shear thickening model (i.e., unified viscosity model) was compared with shear-thinning behavior only. In addition, shear thinning behavior parameters in Flory-Huggins equation were concluded and included in the model. Moreover, polymer adsorption parameters (Langmuir adsorption parameters) were also concluded and included in the model. Different injection schemes were compared to select the best combinations of injection of polymer and gelant solutions. For all injection schemes, a 0.23 PV was injected inside the reservoir, starting with 0.058 PV of water floods, followed by scheduled injected fluids. Input polymer and gel parameters were used from published literatures with some modifications to polymer shear thinning parameters and polymer adsorption parameters. The main purpose of this study was to design the gel treatment that might yield higher recovery factor and higher incremental oil production based on investigating different parameters. The parameters includes the effect of polymer rheology, the effect of salinity on polymer viscosity and polymer adsorption, presence of the divalent cations (hardness), injection schemes, wettability of the formation, the presence of clay and its effects on the removal of crosslinkers from the gelant solution, mobility ratio, dip angle and gravity segregation of the fluids, and the effect of the skin factor in the injection well. Abstract: This study investigates the effects of different parameters on the in-situ gelation of a polyacrylamide/chromium(VI)/thiourea solution using numerical modeling. The effects of polymer rheology, water salinity of the system on polymer viscosity and polymer adsorption, presence of divalent cations (hardness), injection schemes, wettability of the formation, cation exchange capacity (CEC), mobility ratio, and dip angle of the reservoir were investigated by a 3D model using UTGEL simulator. The injection pattern was one quarter of five-spot with eight layers. The model had two thief zones that were located in the middle of the model. The permeability of the thief zones was 1, 500 md, with a permeability contrast (heterogeneity) of 15/1. The ratio of vertical to horizontal permeability was 0.01. The results showed that regardless the salinity of the brine, considering both shear-thinning and shear-thickening behavior (i.e., UVM model) always yielded better results than assuming shear-thinning behavior only. The results also showed that the higher the salinity of the system, the lower the recovery factor. Thus, low salinity post-treatment water improved the results, especially when the initial salinity of the system was too high. Moreover, the presence of divalent cations (hardness) affected the efficiency of gel treatment; therefore, low-salinity chase water floods improved the recovery. In addition, if the pore volume of the post-treatment water was not high, the optimum injection scheme would be the injection of the polymer solution before the gel treatment. However, if the pore volume of the post-treatment water was high, the ultimate oil recovery would not affected by the injection scheme and the treatment using only the gel would be the most viable scheme. In addition, damage in the low-permeability layer adjacent to the thief zone was significant for oil-wet conditions compared to water-wet conditions. Furthermore, the presence of the clays in the formation (i.e., increasing the cation exchange capacity) lowers the amount of the crosslinkers that are available for polymer to form gel due to the removal of the crosslinkers from the gelant solution. Therefore, no gel will form with a high value of CEC. Increasing the mobility ratio will lower the efficiency of gel treatment; thus, injection of the polymer solution after the gel treatment was the best option. The dip angle from the injector to the producer assisted the gel placement, which resulted in high oil recovery. Finally, the effect of the skin factor should be taken into consideration in designing the gel treatment, especially at high injection rate.